1950
DOI: 10.1063/1.1699765
|View full text |Cite
|
Sign up to set email alerts
|

The Static Electrification of Dust Particles on Dispersion into a Cloud

Abstract: An extensive study of the charge and size distribution of particles from 0.5 to 30 microns radius in dust clouds of diverse exemplary types dispersed in air under a variety of conditions ranging from blowing with minimum of turbulence to conditions of violent and maximum impact with various types of surfaces was made using adaptations of the Hopper and Laby modification of the oil drop experiment. It was observed that all dusts, including homogeneous dusts with no impacts on solid surfaces, were charged. In ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1952
1952
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…This size dependence has been best demonstrated in laboratory experiments involving sand cascading Kok and Lacks 2009;Lacks and Levandovsky 2007, Forward et al 2009a, 2009bBilici et al 2014). However, not all experimental studies reproduce this behaviour (Trigwell et al 2003;Sowinski et al 2010;Kunkel 1950). It should also be noted that in many of these electrification studies multiple particle interactions are involved, including particle-wall interactions , and material purity (surface composition) is not well controlled.…”
Section: Particulate Size Dependencementioning
confidence: 98%
See 1 more Smart Citation
“…This size dependence has been best demonstrated in laboratory experiments involving sand cascading Kok and Lacks 2009;Lacks and Levandovsky 2007, Forward et al 2009a, 2009bBilici et al 2014). However, not all experimental studies reproduce this behaviour (Trigwell et al 2003;Sowinski et al 2010;Kunkel 1950). It should also be noted that in many of these electrification studies multiple particle interactions are involved, including particle-wall interactions , and material purity (surface composition) is not well controlled.…”
Section: Particulate Size Dependencementioning
confidence: 98%
“…They rely upon the application of an electric field and the drift of electrified dust grains. The field induced drift velocity can be determined using optical or laser systems to study particle trajectories (Kunkel 1950;Mazumder et al 1991) or by extracting dust onto a surface . The fieldinduced drift velocity will be proportional to the electrical force and therefore the electric charge and polarity of the dust grains.…”
Section: Surface Charge Densitymentioning
confidence: 99%
“…Proportionality between the average charge and the square of the radius was reported by Rosenblum (8) for dust or mist, and inferred by Daniel and Brackett (3) for fine silica dust. I<unkel (6) found the charge on dust particles to increase somewhat less rapidly than the square of the radius. Arendt and ICallmann (1) found the limiting charge carried by small fog particles in regions of high ion density to be approximately proportional to the radius.Typical plots of the average radius for each size group against the average charge per particle (calculated with disregard to sign) are shown in Fig.…”
Section: T H E Determination O F Charge Distribui'ionmentioning
confidence: 99%
“…The results for quartz and mica aerosols dispersed by the fluidized bed generator suggest that the principal means of charging may be contact electrification involving the bronze beads of the bed itself. Kunkel(1950) found that particles of the various nonmetallic minerals that he tested "universally received a negative charge" when separated from contact with metal surfaces; but when the surfaces and the particles themselves were of the same material, charging was found to be symmetrical. He also noted that "the asymmetry is exhibited more strongly by the larger particles."…”
Section: Discussionmentioning
confidence: 99%